2015
DOI: 10.18632/oncotarget.5369
|View full text |Cite
|
Sign up to set email alerts
|

Good syndrome presenting with CD8+ T-Cell large granular lymphocyte leukemia

Abstract: Good Syndrome is an adult-onset combined immunodeficiency defined by hypogammaglobulinemia, low or absent number of B cells, T cell deficiency and thymic tumor. We have characterized CD8+ T cells from a patient with Good syndrome that presented with CD8+T-cell large granular lymphocytic leukemia (LGL). Characterization of peripheral blood CD8+ T cells revealed that majority of CD8+ T cells were terminally differentiated effector memory phenotype (TEMRA; CD8+CCR7-CD45RA+), and were PD-1high (CD279), ICOSlow (CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…T-LGLL clonotypes are known to overexpress cytotoxic and T cell activation-associated genes in comparison with their healthy reactive counterparts 44 , 45 . Here, we also found exhaustion-associated genes, such as LAG3 and TIGIT , among the most upregulated genes between T-LGLL and hyperexpanded cells in healthy controls, but not the previously found PDCD1 ( PD1 ) and HAVCR2 ( TIM-3 ) 44 , 45 . Our in vitro validation suggested that TCR ligation fails to trigger normal degranulation and cytokine production in the T-LGLL clonotypes.…”
Section: Discussionmentioning
confidence: 99%
“…T-LGLL clonotypes are known to overexpress cytotoxic and T cell activation-associated genes in comparison with their healthy reactive counterparts 44 , 45 . Here, we also found exhaustion-associated genes, such as LAG3 and TIGIT , among the most upregulated genes between T-LGLL and hyperexpanded cells in healthy controls, but not the previously found PDCD1 ( PD1 ) and HAVCR2 ( TIM-3 ) 44 , 45 . Our in vitro validation suggested that TCR ligation fails to trigger normal degranulation and cytokine production in the T-LGLL clonotypes.…”
Section: Discussionmentioning
confidence: 99%
“…T-LGL cells express pan-T-antigens, programmed cell death 1 (PD-1), some NK-cell associated molecules, cytotoxic granules (containing perforin and granzymes) and lack the CD28 co-stimulatory receptor. Detection of CD45RA and further markers of T-cell differentiation suggest a terminally differentiated effector memory (T EM-RA ) phenotype (128,(186)(187)(188). T EM-RA cells are featured by the absence of CCR7, and accordingly, most T-LGL cases in these studies did not show tumor cell expression of CCR7.…”
Section: T-cell Large Granular Lymphocytic Leukemia (T-lgl)mentioning
confidence: 76%
“…The occurrence of low Hgb and high MCV has been reported in two case studies of T-LGL leukemia and an associated disease, but not in the context of STAT3 mutation status. 64,65 A previous study found that STAT3 SH2 domain mutation is correlated with smaller granular lymphocytes in T-LGL leukemia. 66 In particular, a small subset of four patients with unusually small mean lymphocyte diameter all had D661Y mutation (one was Y640F/D661Y) with anemia (two of them were diagnosed with PRCA).…”
Section: Discussionmentioning
confidence: 98%